New echocardiographic indexes for evaluating cardiac function in idiopathic pulmonary arterial hypertension using three-dimensional echocardiography. Issue 3 (1st June 2016) - Yao, Haohua; Zhou, Daxin; Kong, Dehong; Pan, Cuizhen; Dong, Lili; Wang, Yongshi; Shu, Xianhong
Abstract : Purpose Noninvasive real-time three-dimensional echocardiography (RT3DE) was utilized to explore new indexes for evaluating cardiac function in patients with idiopathic pulmonary arterial hypertension (IPAH). Methods Parameters of cardiac function were evaluated in 24 patients with IPAH and 24 normal control subjects. End-systolic volume (ESV), enddiastolic volume (EDV), and ejection fractions (EFs) of the right and left ventricles (RV, LV, respectively) were measured using a four-dimensional RV and LV quantification method. Right heart catheterization was performed in IPAH patients within one day of the RT3DE examination to obtain measurements of pulmonary vascular resistance (PVR). A 6-minute walk test (6MWT) was also performed within 48 hours. Results RT3DE showed RV volumes were increased while LV volumes were decreased in IPAH patients as compared to volumes in normal control subjects ( P < 0.001, respectively). Additionally, the RVEFs in IPAH patients were significantly lower compared to those in control individuals; however, the two groups showed no difference in LVEF. We then termed RVEDV/LVEDV and RVESV/LVESV as "new indexes, " and found both values were higher in IPAH patients compared to control subjects. A linear regression analysis revealed that neither RVEDV nor RVESV, but rather LVEDV and LVESV negatively correlated with PVR and results on the 6MWT. RVEF correlated negatively with PVR. Both "new indexes" showed a significant positive correlation with PVR and 6MWT results. Conclusions Our results suggest that evaluation of biventricular volume and function using RT3DE might be useful for non-invasive assessment of cardiac function in IPAH.